Crystal structure of bis(η(5)-cyclopentadienyl)(2,3-diethylbutane-1,4-diyl)hafnium(IV) - Burlakov, Vladimir V. (Acta Crystallogr E Crystallogr Commun, 2015)
The title compound, [Hf(C(5)H(5))(2)(C(8)H(16))], proves a structural motif of hafnacyclopentane besides the coordination of two cyclopentadienyl ligands in an η(5)-fashion. The hafnacyclopentane ring has a twist conformation and is substituted by two ethyl groups in the β,β′-positions, which are trans orientated to each other. One cyclopentadienyl ring and one ethyl group are each disordered over two positions with site-occupancy ratios of 0.679 (15):0.321 (15) and 0.702 (18):0.298 (18), respectively.